Careful Words: Nursing, Language, and Emotion in Papua New Guinea. Issue 8 (17th November 2017) - Andersen, Barbara
ABSTRACT: Papua New Guinean nurses work in a sociomedical system in which cultural and linguistic diversity are matters of pressing concern. Using data drawn from ethnographic research with PNG nursing students, I show how nursing education socializes nurses to take stances toward language and communication that impact their care practices. I argue that nurses' use of language is shaped by their ethical commitments as educated Christians and indigenous concerns about the links between language, emotion, and health. In a resource-poor setting where health workers risk blame for structural inequalities, this "ethical metapragmatics" is an important but neglected facet of care work.